CHARACTERISTICS OF STRABISMUS OPERATION AT SANGLAH RSUP DENPASAR IN 2019 - 2020 - suari, ni nyoman trihasti; Surasmiati, Ni Made Ayu; Suryathi, Ni Made Ari; Kusumadjaja, Made Agus (E-Jurnal Medika Udayana; Vol 13 No 10 (2024): E-Jurnal Medika Udayana, 2024)
The eye is one of the important senses for humans, through the eye, human receive visual information that is used to carry out various activities. Perfect eyes are everyone's dream, but it is not always owned because the eyes can also experience abnormalities, one of which is strabismus or crossed eyes. Strabismus is a condition in which the eyeballs are not in the same direction. This study aims to determine the characteristics of strabismus surgery patients based on gender, age, deviation direction, degree of deviation, and surgery. This research is a descriptive research with cross-sectional design. Total sampling was used as a sampling technique. Data was collected using patient medical records at Sanglah Hospital Denpasar in 2019 - 2020. Patients with age <15 years with the highest percentage at 51.3%. Based on the gender, 51.4% of the patients are female. The direction of deviation of esotropia was the most common type (51.4%) with a degree of deviation of 30 – 45 PD (56.7%). The most frequently performed surgery was two-muscle recession as much as 35.1 %. Keywords : Strabismus, surgery, deviation